Glimpses of Hope: Reflections on Journeying with Survivors of Clergy Sexual Abuse - Williams, Mark J. (Journal of Anglican studies, 2024)
Drawing on Roman Catholic and ecumenical expertise, this article takes an honest look at the experiences and hopes of those abused. Many in the churches assume that victims seek financial compensation or legal redress. However, research indicates that many victims primarily seek truth and justice as a means of closure and that their struggles with church leadership arise when truth and justice are repeatedly withheld. This makes forgiveness near-impossible and often results in the victim being re-traumatized by the systemic re-abuse they experience. Ultimately, there is no substitute for full and genuine meeting with victims, which requires the church to lay aside its power and authority and engage with humility and proper deference to the victims abused at the hands of the church. Without such openness, the victims cannot move on, and neither can the churches.